Case Report: Exacerbation of Relapses Following mRNA COVID-19 Vaccination in Multiple Sclerosis: A Case Series - Quintanilla-Bordás, Carlos; Gascón-Gimenez, Francisco; Alcalá, Carmen; Payá, María; Mallada, Javier; Silla, Raquel; Carratalà-Boscà, Sara; Gasque-Rubio, Raquel; Castillo, Jessica; Casanova, Bonaventura (Frontiers in Neurology, 2022)
Introduction mRNA coronavirus disease 2019 (COVID-19) vaccination has been widely used to arrest the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. Rarely, autoimmune events such as relapses in patients with multiple sclerosis (MS) have been reported after vaccination. However, the possible effects of vaccination in a patient already experiencing the symptoms of a relapse represent an unusual scenario that has not been described. Patients and Methods This is a retrospective case series of four patients from three major tertiary referral centers that received mRNA COVID-19 vaccination after starting with symptoms of acute demyelination of the central nervous system due to non-recognized MS. A detailed description of each case, including MRI studies, serum light-neurofilament levels, and cerebrospinal fluid (CSF) cytokine profile, is provided. Case Description All patients presented exacerbation of ongoing symptoms after vaccination (range 14–112 days first dose). All patients presented MRI features suggestive of highly active MS and fulfilled McDonald 2017 criteria at the time of presentation. All patients presented high serum light-neurofilament levels and oligoclonal G bands restricted to the CSF. Higher levels of interleukin-6 in the CSF were present in the more severe cases. Discussion We describe exacerbation of relapses after mRNA COVID-19 vaccination. We hypothesize RNA sensors such as Toll-like receptor 7 may be activated and contribute to amplify the inflammatory response during a relapse. Conclusion Patients should seek medical attention if experiencing acute neurological symptoms, especially before vaccination. Fast diagnostic procedures and prompt treatment should be performed in these patients. Pharmacovigilance and further study are warranted to confirm causality.